Unraveling Cellular Phenotypes of Novel TorsinA/TOR1A Mutations. Issue 9 (17th July 2014) - Vulinovic, Franca; Lohmann, Katja; Rakovic, Aleksandar; Capetian, Philipp; Alvarez‐Fischer, Daniel; Schmidt, Alexander; Weißbach, Anne; Erogullari, Alev; Kaiser, Frank J.; Wiegers, Karin; Ferbert, Andreas; Rolfs, Arndt; et al.
<x xml:space="preserve">Abstract</x> We report two new putative TOR1A mutations (p.A14_P15del and p.E121K) that we examined functionally in comparison with wildtype protein. Our findings demonstrate functional changes on different levels.Western blot analysis of cross‐linking experiments with formaldehyde (FA) and quantification of TOR1A levels in SH‐SY5Y cells expressing TOR1A show significantly enhanced dimerization at 74 kDa for p.A14_P15del mutant TOR1A (NT: non‐treated). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>